Job status differences in employees' judgment of organisatiqnal restructuring policy effectiveness (2008)
The study was designed to examine employees' status differences on their judgment of organizational restructuring policy effectiveness. The survey research was carried out in three companies in Lagos Metropolis, Nigeria. The companies were restructuring their operations by adopting a Total Quality Management Policy. A total of 217 respondents took part in the study. In the sample size, 146 are male respondents, while the remaining 71 are females. Questionnaires containing Perceived TQM Implementation Effectiveness (PTIE) scale and demographic characteristics sections were used for data collection. It was hypothesized that there will be significant differences in employees' judgment of the restructuring policy effectiveness based on their job statuses. The One-way Anova was used to test the hypothesis, which was confirmed by the results obtained (P<.05). It was concluded that senior level employees perceived the restructuring policy as effective more than the middle and lower level employees. Decentralisation of authority relations to empower lower level employees was consequently recommended